DIFFERENCES IN SELF-REGULATED LEARNING AMONG STUDENTS IN TERMS OF GENDER - Refika, Cindy (Causalita, 2023)
Self-regulated learningare important skills that enable students to control, manage and monitor their own learning. This research aims to determine the differences in self-regulated learning in male and female students. This research uses a comparative quantitative method with t-test analysis. Data was collected through a questionnaire based on a scale adapted from Lili Nur Indah Sari's 2013 Self-regulated Learning scale based on aspects of self-regulated learning by Zimmerman (1989). The sampling technique was proportionate random sampling, totaling 75 people consisting of 26 men and 49 women. The results show that there is a significant difference between the self-regulated learning of male and female students, namely that female students are higher.